2020
DOI: 10.1111/jnc.15139
|View full text |Cite
|
Sign up to set email alerts
|

Detergent‐insoluble inclusion constitutes the first pathology in PFN1 transgenic rats

Abstract: Mutation of profilin 1 (PFN1) can cause amyotrophic lateral sclerosis (ALS). To assess how PFN1 mutation causes the disease, we created transgenic rats with human genomic DNA that harbors both the coding and the regulatory sequences of the human PFN1 gene. Selected transgenic lines expressed human PFN1 with or without the pathogenic mutation C71G at a moderate and a comparable level and in the similar pattern of spatial and temporal expression to rat endogenous PFN1. The artificial effects of arbitrary transge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Other transgenic mouse models expressing strong levels of C71G or G118V mutant PFN1, under the control of neuronal Thy1.2 or PrP promoters, showed strong motor phenotypes and decreased survival, and loss of motor neurons in the spinal cord, resembling ALS [ 22 , 23 , 24 , 25 ]. We did not observe a strong disease phenotype using our lentiviral transgenesis approach based on the expression of PFN1 under the control of the human ubiquitin C promoter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other transgenic mouse models expressing strong levels of C71G or G118V mutant PFN1, under the control of neuronal Thy1.2 or PrP promoters, showed strong motor phenotypes and decreased survival, and loss of motor neurons in the spinal cord, resembling ALS [ 22 , 23 , 24 , 25 ]. We did not observe a strong disease phenotype using our lentiviral transgenesis approach based on the expression of PFN1 under the control of the human ubiquitin C promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Whether PFN1 mutations contribute to an ALS phenotype through a gain- or a loss-of-function is a source of debate [ 2 , 13 , 21 ]. However, the evidence supporting a gain-of-function mechanism is far more robust, since the transgenic rodents expressing mutant (C71G, G118V) PFN1 forms elicit motor neuron degeneration and ALS-like phenotypes [ 22 , 23 , 24 , 25 ], whereas heterozygous Pfn1 knockout mice do not show overt motor phenotypes [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Exome sequencing studies reveal 8 mutations in the PFN1 gene in both familial and sporadic ALS cases (C71G, G118V, M114T, E117G, T109M, R136W, A20T, Q139L) (Figure 6.1; Wu et al, 2012;Chen et al, 2013;Ingre et al, 2013;Smith et al, 2015;Alkam et al, 2017). The PFN1-associated ALS pathology is reproducible in several mouse and rat models (Yang et al, 2016;Fil et al, 2017;Barham et al, 2018;Brettle et al, 2019;Yuan et al, 2020). The expression of ALS-PFN1 mutants evokes cytoskeletal and morphological defects in primary neurons, such as abnormally low ratios of F-/G-actin, shorter dendrites and integrity-impaired axons, which undergo Wallerian degeneration over time (Figure 6.2; Wu et al, 2012;Yang et al, 2016;Fil et al, 2017).…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 98%
“…Importantly this paper also showed that profilin has the capacity to directly bind microtubules in vitro in an interaction independent of either the actin or PLP‐binding surfaces but compromised by ALS‐related mutations characterized previously (Wu et al, 2012). Current studies in this area are now focused to understand how the profile of this devastating disease correlates with an inability of profilin to directly associate with microtubules (e.g., Brettle et al, 2019; Yuan et al, 2020).…”
Section: Profilin 1 and Microtubule Organizationmentioning
confidence: 99%